Balanço tendencial das dissertações e teses sobre dificuldades de aprendizagem (1987/2010) - Oliveira, Angelita Mendes Ramos de (2012)
The main goal of this present study, carried out in 2012 was to investigate the tendencies of educational research in regard to what is called learning disabilities by means of 183 thesis and dissertation that approaches the learning disabilities, deposit at CAPES s Bank of Thesis between 1987/2010, based on the contribution from Williams (1980), Bourdieu (2007) and Bourdieu e Passeron (2010), we pursuit the answers for the following questions: who produced; when it was developed the scientific narrative from dissertation and thesis that investigated the poor academic performance in the perspective of learning disabilities; in which way these investigations were carried out; and at last, if the tendency to input the poor academic (scholarship) performance to so-called learning disabilities overruled during the entire period investigated or if a critical perspective represented by the studies of Patto (1999) and Collares & Moyses (1996) started to influence over this production. The results show that, even besides the dissemination rise against the practice of attributing to the students the scholarship low gain, still prevails the traditional conception , although the production based on critical perspective has grown in the period analyzed